2017
DOI: 10.1016/j.foodpol.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Ten striking facts about agricultural input use in Sub-Saharan Africa

Abstract: Conventional wisdom holds that Sub-Saharan African farmers use few modern inputs despite the fact that most poverty-reducing agricultural growth in the region is expected to come largely from expanded use of inputs that embody improved technologies, particularly improved seed, fertilizers and other agro-chemicals, machinery, and irrigation. Yet following several years of high food prices, concerted policy efforts to intensify fertilizer and hybrid seed use, and increased public and private investment in agricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
357
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(379 citation statements)
references
References 46 publications
20
357
0
2
Order By: Relevance
“…Overall, only 41% of the total farmers applied pesticides in any of their food crops (Table 2). This figure is, however, higher than 33% and 16.3% for Nigeria and for the 6 African countries combined, respectively, as reported by Sheahan and Barrett [10]. The pesticide use rate reported in column 5 is for all the farmers (i.e., pesticide users and non-users) that produce each major food crop, which shows the overall level of pesticide use in the study areas.…”
Section: Level and Extent Of Pesticide Use By Major Food Cropsmentioning
confidence: 58%
See 1 more Smart Citation
“…Overall, only 41% of the total farmers applied pesticides in any of their food crops (Table 2). This figure is, however, higher than 33% and 16.3% for Nigeria and for the 6 African countries combined, respectively, as reported by Sheahan and Barrett [10]. The pesticide use rate reported in column 5 is for all the farmers (i.e., pesticide users and non-users) that produce each major food crop, which shows the overall level of pesticide use in the study areas.…”
Section: Level and Extent Of Pesticide Use By Major Food Cropsmentioning
confidence: 58%
“…Table 1 presents the definition, measurement, and summary statistics of all the variables used in the econometric model. The choice of these variables was based on the literature and justification thereof [4,10,[19][20][21]25,26]. All price variables used in this study were reported by the farmers for purchase of inputs and sale of outputs.…”
Section: Variablesmentioning
confidence: 99%
“…The LSMS-ISA data of Uganda have been used in a wide range of livelihood studies both on food security, for example on effects of physical activities on food consumption and on the use of complementary indices for food security (Mathiassen and Hollema 2014;Hjelm et al 2016) and on agriculture (e.g. Sheahan and Barrett 2017;Gilbert et al 2017;Palacios-Lopez et al 2017). The comprehensive cross-country coverage and the detailed agricultural survey of the LSMS provided an adequate dataset for the purpose of our study.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, the drought in 2015 and 2016 resulted in food shortage for over ten million people, showing the low level of surplus food production in the country (FAO 2016). This is partly the result of the limited use of agricultural technologies in Ethiopia, as in most other sub-Saharan African countries (Sheahan and Barrett 2017). One of the most important agricultural technologies in this respect is seed.…”
Section: Introductionmentioning
confidence: 99%